Brief Report–Modeling Media Use: How Parents’ and Other Adults’ Posting Behaviors Relate to Young Adolescents’ Posting Behaviors - Reich, Stephanie M.; Starks, Allison; Santer, Nicholas; Manago, Adriana (Frontiers in Human Dynamics, 2021)
Middle school is a period when young adolescents become more engaged with social media and adults become increasingly concerned about such use. Although research finds that parents often post about their children on social media, little is known about how adults’ social media behaviors relate to youths’ online behaviors. We surveyed 466 middle-school students about their social media habits, privacy-respecting behaviors, and their parents’, other adults’, and their own posting behaviors on social media. While 68% used social media, only 41% posted pictures. Of those, 33.5% also had parents and/or adults that posted about them. Using this subset, we found that adults’ privacy-respecting behaviors (e.g., asking permission to post, showing post first) were significantly connected to youth using these same privacy-respecting behaviors when posting on social media. Like many areas of development, young adolescents may learn about social media use by modeling their parents’ and other adults’ behaviors.